In Vitro Bioaccessibility of Edible Seaweed Proteins from the Chilean Coast and Proteins from the Novel Seaweed-Derived Mycoprotein - Catalina Landeta-Salgado; Javiera Munizaga; María Paz González-Troncoso; Anamaría Daza-Sanchez; Irene Martínez; María Elena Lienqueo (Molecules)
Seaweed biomass is globally underutilized as a source of proteins despite its nutritional potential, with much of its use focused on hydrocolloid extraction. This study evaluated the nutritional quality and digestibility of protein and amino acids from two brown seaweeds (Durvillaea spp. and Macrocystis pyrifera), one green seaweed (Ulva spp.), and a novel mycoprotein derived from Durvillaea spp. through fungal fermentation. Using an in vitro gastrointestinal digestion Megazyme assay kit, protein digestibility-corrected amino acid scores (PDCAASs) and digestible indispensable amino acid scores (DIASSs) were determined. Compared with seaweeds, seaweed-derived mycoprotein presented significantly greater protein contents (~33%) and amino acid profiles (2.2 times greater than those of Durvillaea spp. and M. pyrifera), with greater digestibility (~100%) than seaweeds (<60%). The PDCAAS values were 0.37, 0.41, 0.53, and 0.89 for Ulva spp., Macrocystis pyrifera, Durvillaea spp., and mycoproteins, respectively. The DIASSs highlighted the superior nutritional quality of the mycoprotein, particularly for lysine (0.59) and histidine (0.67). SDS-PAGE revealed soluble peptides (<25 kDa) in Durvillaea spp., Macrocystis pyrifera, and mycoproteins, whereas Ulva spp. proteins exhibited limited solubility due to structural aggregation. These findings highlight the need to characterize the nutritional properties of edible seaweeds in Chile further and emphasize the importance of optimized processing techniques, such as fermentation or bioconversion, to improve the nutritional potential of seaweeds and develop high-quality food ingredients for diverse applications.